Investigation and optimization of polarization properties of self-assembled carbon nanotube films. (7th May 2022) - Zhang, Hui; Wang, Yibin; Zhang, Peng; Hou, Huwang; Zhao, Yang
Abstract: Super-aligned carbon nanotubes (CNTs) film has strong anisotropy to light propagation. In order to better integrate the self-assembled CNTs into microelectromechanical system (MEMS) for polarization applications, some inherent impacts on polarization properties of CNT film were investigated. We described the polarization effects of the film thickness variation in detail, giving an optimum thickness range which is around 700–800 nm. The amorphous carbon content of CNT film was reduced by oxidation process where the transmittance increased by almost 4 folds. The alignment of CNT arrangement was optimized from 0.41 (Chebyshev orientation parameter) to 0.54 by manipulating the C2 H4 flow rate from 54 to 80 sccm. More specifically, a sample possessing a degree of polarization up to 99% and transmittance over 45% was obtained through proper regulations. The validated optimization makes the aligned CNT films more feasible and valuable for the integration of the CNT polarimeters with MEMS technology.